Reportaże z pamięci. O rekonstruowaniu rzeczywistości minionej w filmach dokumentalnych Mariana Marzyńskiego - Jazdon, Mikołaj (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
Reports from Remembering. Marian Marzyński’s Documentary Reconstructions of the Past Reality The article focuses on autobiographical films by Polish-American documentary filmmaker whose most personal project is Never Forget to Lie (2012) about Jews rescued from the Warsaw ghetto in their early childhood. Marzyński is a Holocaust survivor himself and a television reporter who emigrated from communist Poland in 1969. He has been gradually transforming the style of the documentary films he made in the West to make them more and more personal by referring to his biography. Marzyński’s cinéma vérité techniques include initiating emotional in-front-of-the-camera interviews with Holocaust survivors and witnesses of History in the meaningful surrounding of historical places. In this way, the filmmaker makes the architecture, landscape and personal objects “speak” about the past or uses them to stimulate the memory of the interviewed people. The only quoted film material, or found footage, comes from his own archives, where he has been collecting his released documentaries together with never used scenes and takes.